Through the Clock's Workings - Barker, Amy (Sydney University Press, 2009)
A world first! The first remixed and remixable anthology of literature.This anthology of short stories is not some textual tome, frozen in time and space. It is alive, evolving organically in a constant state of flux. Why? Because each story is available under a Creative Commons licence, giving you rights to share and reuse the book as you see fit.